2020
DOI: 10.7322/jhgd.v30.11063
|View full text |Cite
|
Sign up to set email alerts
|

Trends in case-fatality rates of COVID-19 in the World, between 2019 - 2020

Abstract: Introduction: CoV infections can potentially cause from a simple cold to a severe respiratory syndrome, such as the Severe Acute Respiratory Syndrome and the Middle East Respiratory Syndrome (MERS-CoV). The COVID-19 created a new reality for global healthcare models. Objetive: To evaluate trends in case fatality rates of COVID-19 in the World. Methods: We conducted a population based time-series study using public and official data of cases and deaths from COVID-19 in Argentina, Australia, Brazil, Chile, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(24 reference statements)
0
7
0
3
Order By: Relevance
“…This value falls below the expected range reported previously by Ghayda et al (2020) [ 47 ]. Previous studies conducted in 2020 reported global CFR of 3.4% [ 48 ] and 3.1% [ 49 ]. CFR values for COVID-19 can be dynamic, with suggestions that it might be difficult to accurately determine [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This value falls below the expected range reported previously by Ghayda et al (2020) [ 47 ]. Previous studies conducted in 2020 reported global CFR of 3.4% [ 48 ] and 3.1% [ 49 ]. CFR values for COVID-19 can be dynamic, with suggestions that it might be difficult to accurately determine [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trends in lethality, mortality, and incidence rates may change according to the region. The stationary trends in lethality rates found during the first wave followed the global trend of lethality of COVID-19 that remained stationary between December 31, 2019, and August 31, 2020 50 .…”
Section: Time Analysismentioning
confidence: 68%
“…According to Bernal et al, 50 , the COVID-19 pandemic is still in a global progression phase. In the State of Espírito Santo, this same trend is observed today.…”
Section: Spatial Analysismentioning
confidence: 99%
“…Tal patógeno está relacionado à propagação da COVID-19, considerada pandemia pela Organização Mundial da Saúde (OMS), em março de 2020. Desde então, grande foi o impacto do novo coronavírus na saúde pública, em razão do alto número de casos relatados e elevada mortalidade em um curto período de tempo, sendo o distanciamento social a principal estratégia para mitigar a propagação (Jiang et al, 2020;Santos et al, 2020;Bernal, Siqueira, Adami, & Santos, 2020).…”
Section: Introductionunclassified